Angiotensin Converting Enzyme (ACE) gene I/D polymorphism genotypes and ACE levels of serum and synovial fluid of patients with osteoarthritis - Sayin, B.E.; Bayram, B.; Turkoğlu, Z.; Keles?emur U.; Mutlu F. (My University, 2009)
This study was conducted to determine the association between angiotensin converting enzyme gene I/D polymorphism genotypes and angiotensin converting enzyme levels of serum and synovial fluid of patients with osteoarthritis. Genomic DNA obtained from 42 persons (27 patients with osteoarthritis and 15 healthy controls) was used in the study. DNA was multiplied by polymerase chain reaction using I and D allele-specific primers. Polymerase chain reaction products were assessed with UV transilluminator by being exposed to 2% agarose gel electrophoresis. Synovial fluid was obtained by needle aspiration from patients with knee effusion and collected during the arthroscopic procedures in cases with osteoarthritis and during the trauma surgery in cases without osteoarthritis. Angiotensin converting enzyme levels of serum and synovial fluid were determined by using ELISA kit. Angiotensin converting enzyme serum and synovial fluid levels were higher in patients with osteoarthritis than controls but the difference was not significant (p>0.05). According to genotypes there was also no significant difference between angiotensin converting enzyme levels of serum and synovial fluid of the groups (p>0.05). In this study, no association was determined between angiotensin converting enzyme gene I/D polymorphism genotypes, and serum and synovial fluid angiotensin converting enzyme levels in osteoarthritis patients.
Keywords: ACE; Osteoarthritis; Synovial fluid